Crisis economics: perilous liquidity - Schultz, Steven Brandon (My University, 2013)
No abstract provided
Thesis (M.M. (Finance & Investment))--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Business Administration, 2013.
Keywords: Financial crises; Global financial crisis